Nickel‐Catalyzed Unsymmetrical Bis‐Allylation of Alkynes. Issue 17 (15th March 2023) - Li, Ying; Zhang, Wei‐Song; Yang, Sa‐Na; Wang, Xiao‐Yu; Liu, Yan; Ji, Ding‐Wei; Chen, Qing‐An
Abstract: The catalytic bis‐allylation of alkynes is an important but challenging protocol to construct all‐carbon tetra‐substituted alkenes. Particularly, the catalytic unsymmetrical bis‐allylation of alkynes remains as an underexplored task to date. We herein report an unprecedented unsymmetrical bis‐allylation by simultaneously utilizing electrophilic trifluoromethyl alkene and nucleophilic allylboronate as the allylic reagents. With the aid of robust Ni 0 /NHC catalysis, valuable skipped trienes can be obtained in high regio‐ and stereo‐selectivities under mild conditions. Mechanistic studies indicate that the reaction may proceed through a β‐fluorine elimination of a nickelacycle followed by a transmetalation step with allylboronate. The present method exhibits a good tolerance of various functional groups. Besides, the skipped triene products can undergo an array of elaborate transformations, which highlights the potential applications of this strategy. Abstract : An efficient unsymmetrical bis‐allylation of alkynes has been developed by simultaneously utilizing electrophilic trifluoromethyl alkenes and nucleophilic allylboronates as the allylic reagents. With the aid of a robust Ni 0 /NHC catalysis, valuable skipped trienes can be obtained in high regio‐ and stereo‐selectivities under mild conditions.